1994
DOI: 10.1111/j.1476-5381.1994.tb14035.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of GR117289, a novel angiotensin AT1 receptor antagonist

Abstract: 1 The effect of GRI 17289, an angiotensin AT, receptor antagonist, on diastolic blood pressure (DBP) was determined in angiotensin-dependent and angiotensin-independent models of hypertension in rats. In addition, the antagonist profile of GRi 17289 at angiotensin AT1 receptors was determined in conscious renal hypertensive rats and conscious normotensive rats, dogs and marmosets. 2 Intra-arterial and oral administration of GRI17289 (0.3-3mgkg-', i.a.; 1-10mgkg-', p.o.) to 6-day left renal artery ligated hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…Results are shown in Figure 6. Discussion GRI17289 and GR138950 reduce blood pressure in rats in which it is elevated due to activation of the renin-angiotensin system (Hilditch etal., 1993;1995). However, their antagonist profiles against pressor responses produced byAII in conscious hypertensive and normotensive rats do not temporally correlate with their antihypertensive activities.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Results are shown in Figure 6. Discussion GRI17289 and GR138950 reduce blood pressure in rats in which it is elevated due to activation of the renin-angiotensin system (Hilditch etal., 1993;1995). However, their antagonist profiles against pressor responses produced byAII in conscious hypertensive and normotensive rats do not temporally correlate with their antihypertensive activities.…”
Section: Resultsmentioning
confidence: 95%
“…However, their antagonist profiles against pressor responses produced byAII in conscious hypertensive and normotensive rats do not temporally correlate with their antihypertensive activities. Previously, in order to explain this disparity, we have suggested that compounds like GRI 17289 and GR138950 might interact with receptors within the central nervous system, or deep within the vascular wall where they might inhibit the contribution made by the local renin-angiotensin system to the regulation of vascular tone 1995). In the present experiments, we have attempted to establish the extent to which blockade of All, generated locally in the vasculature, plays a role in this disparity.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations